KẾT QUẢ NGHIÊN CỨU SỤT LÚN ĐẤT Ở HÀ TRUNG - HẬU LỘC TỈNH THANH HOÁ - Túc, Nguyễn Đăng; Thơm, Bùi Văn; Thịnh, Nguyễn Huy (Vietnam Journal of Earth Sciences, 2012)
Study results on ground subsidence in Ha Trung - Hau Loc, Thanh HoaOur work presents investigation results about spatial distribution, development and damage of ground subsidence in Ha Trung - Hau Loc District, Thanh Hoa Province. First, we assess the role of some subsidence-generated factors such as geology-petrology, geomorphology, neo-tectonics, geotechnics-geohydrology, metero-hydrology and human activities. Later, we define the natural reasons for subsidence in some sensitive areas. It is showed that subsidencewould easily occur if there is occurrence of large shaking, strong sub-surface flows or perturbation of ground water level in these areas. Human activities do not play a key role for generating subsidence, but with occurence of civil or industrial wells as well as digging of aquaculture ponds may also impulse the hazard in Ha Trung - Hau Loc and surroundings.